An assessment of the relationship between the level of occupational health and safety and the economic effects achieved on a given positions - Dariusz Smoliński; Leszek Solecki (Economic and Environmental Studies (E&ES), 2016)
This paper aims at evaluating the relationship existing between the level of health and safety of selected types of working position with their economic value. Ten stationary positions in different branches of economics were studied. Estimated costs associated with the work of man, estimated the risk of environmental hazards and determined the effectiveness of the use of the test job. For all the analyzed work positions, the changes introduced in the area of health and safety led to a simultaneous increase in productivity and a decrease in labour cost. It was also revealed that a strong link exists between the OEE index and the level of occupational risks. The research showed that the level of occupational health and safety and the economic value of a given work are strongly connected. Successive waves of modifications ultimately triggered an increase in the OEE, up to a level much higher than that registered before their introduction, as well as a reduction of the labor cost.
Keywords: 15; J8; Q1; 330; shealth and safety; labor costs; the risk of threats; OEE; modifications job